The Prediction of Curcumin Content in the Turmeric Rhizome with Raman Handheld Spectroscopy - I Made Agus Gelgel Wirasuta; Cokorda Istri Tirta Rusmala Dewi; Ni Putu Linda Laksmiani; I Gusti Ayu Made Srinadi; Deddi Prima Putra (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
The quality control of herbal medicine should be started from the determination of the active substance at harvest time. The Raman spectrometry has been used for this propose. The aim of this study is to determine the quantification of curcumin in turmeric rhizome (Curcuma longa Linn.) using Raman spectroscopy combined with multivariate analysis of PLS-R that are expected to provide reference method for quality control in turmeric rhizome, especially for raw materials of Herbal drugs. Parameters that can be used for analysis of curcumin levels on turmeric rhizome obtained using intensity of data Raman and the data obtained from the standard method will be processed with multivariate analysis methods PLS-R. The validation value of quantification result using Raman-PLSR is seen from R2 value of 0.957, RMSEC value of 0,199 and p-value of 0.00. The study showed the developed method could be implemented on to determine the prediction quantification of raw material herbal medicine.Keyword : Curcumin, PLS-R, Turmeric, Raman Spectroscopy